Effect of water on the stress corrosion cracking behavior of API 5L-X52 Steel in E95 Blend - Pedraza Basulto, G. K.; Arizmendi Morquecho, Ana; Cabral Miramontes, José Ángel; Borunda Terrazas, A.; Martínez Villafañe, A.; Chacón Nava, José G. (2013)
The effect of water content (0.5%, 1%, 2%, 5%, 10% y 20 V%) in E95 blend (5 V% gasoline – 95 V% ethanol) on the stress corrosion cracking (SCC) susceptibility of X-52 carbon steel was investigated. Slow strain rate tests (SSRT) coupled with electrochemical noise measurements (ECN) were carried out using a strain rate of 1 X 10-6 s-1. In general, scanning electron microscopy (SEM) observations on fracture surfaces showed a ductile behavior. However, secondary cracking was only observed for specimens exposed to solution containing up to 2 V% water. ECN gave indication of a likely localized corrosion process occurring at low water concentrations, whereas for water content above 2 V%, a uniform corrosion process seems more likely to occur. In addition, the material response immersed into the various solutions was investigated by using linear polarization resistance (LPR) measurements, weight loss and pH measurements. Reasons to explain the behavior found are discussed.